Duty-ratio Based Adaptive Sliding-mode Control Method for Boost Converter in a Hybrid Energy Storage System. (May 2017) - Wang, Bin; Xu, Jun; Yan, Zhen; Cao, Binggang; Yang, Qingxia
Abstract: In this paper, a duty-ratio based adaptive sliding-mode control (SMC) method is proposed for the current tracking control of a boost converter in a battery/supercapacitor (SC) hybrid energy storage system (HESS). The state-space average model is established for the battery/SC HESS. A sliding surface is also defined based on the tracking current error. Furthermore, to deal with unknown disturbances, a state observer is designed based on the estimates of the load resistor, the external input voltage, the inductor current and the output voltage. Adaptation rules are designed based on the state observer and the Lyapunov function. The adaptive duty-ratio is calculated according to the adaptation rules and sliding surface. Experiments are presented to verify the effectiveness of the proposed method. Compared with the PI control strategy, the adaptive SMC method improves up to 20% of the transient time to deal with the load variation. It also reduces 75% of the transient time during start-up of the boost converter in the battery/SC HESS.